On distribution approximation: A simple comparative study on procedural variation of the Zheng test - Dacuycuy, Lawrence B. (Animo Repository, 2005)
The study analyzes the performance of the Zheng test for functional form in different scenarios concerning the distribution approximation of the test statistic. We apply the test statistic for validating simple wage functions.